2001
DOI: 10.1063/1.1377023
|View full text |Cite
|
Sign up to set email alerts
|

Slow domains in semi-insulating GaAs

Abstract: Articles you may be interested inBroadening effects and ergodicity in deep level photothermal spectroscopy of defect states in semi-insulating GaAs: A combined temperature-, pulse-rate-, and time-domain study of defect state kinetics Saturated electric field effect at semi-insulating GaAs-metal junctions studied with a low energy positron beam Semi-insulating GaAs shows current oscillations if a high dc voltage is applied to a sample. These oscillations are caused by traveling high-electric-field domains that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 138 publications
3
15
0
1
Order By: Relevance
“…When the voltage V approaches the threshold level V cr from below, the current I in the structures exhibits oscillations of a relatively small amplitude. Such a behavior of SI-GaAs samples has been observed previously (see, e.g., recent review [2] devoted to the problem of domain instability in SI GaAs). For V ≥ V cr , the current usually oscillates in a broad range of voltages, whereby both regular and irregular variations can be observed.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…When the voltage V approaches the threshold level V cr from below, the current I in the structures exhibits oscillations of a relatively small amplitude. Such a behavior of SI-GaAs samples has been observed previously (see, e.g., recent review [2] devoted to the problem of domain instability in SI GaAs). For V ≥ V cr , the current usually oscillates in a broad range of voltages, whereby both regular and irregular variations can be observed.…”
Section: Resultsmentioning
confidence: 67%
“…As is known, current pulsations of large amplitude in such materials are related to the dynamics of electrical domains (generation, motion along the sample, and damping at the contacts). It is suggested that electrical instability observed in the samples of this type is related to an increase in the rate of trapping carriers by EL2 centers heated by the electric field [2]. The electrical instability of the GaAs cathode in a planar SGDGS was analyzed using both the current and DLE data is shown in fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns in the system are formed due to the coupling of processes of charge transport in two layers, one layer being a linear high-resistance photodetector, while the other layer is a gas discharge domain and is a medium with transport properties that are strongly non-linear. 6,7 At the same time, in the converter cell the discharge gap does not distort the distribution of the current density in the photodetector. The discharge gap, however, can be used to monitor and study quantitatively the spatial distributions of the current because of the emission of visible radiation by the gas.…”
Section: Introductionmentioning
confidence: 96%
“…This effect is well known to exist in some types of semi-insulating GaAs and is due to an increase in the recombination rate of nonequilibrium free carriers in the semiconductor at a high electric field (see, e.g., the review in Ref. [12]. Applying such an electrode in the SGD device may yield complicated spatiotemporal patterns when the voltage of the electrode reaches a critical value [13][14][15].…”
Section: Introductionmentioning
confidence: 97%